Climate change projections in some Asian countries - Challinor, Andrew J. (Earthscan, 2011)
Climate change impacts upon the world's poorest most heavily. It is therefore essential that international development initiatives focus on improving the ability of developing countries to adapt to the effects of climate change. This book, a product of research by the JICA-RI (Research Institute of the Japan International Cooperation Agency), examines climate change adaptation from the perspective of development cooperation in order to provide useful lessons for those engaged in research, policy and practice in this vital area. In this book the editors have brought together a wide range of case studies from across Africa and Asia, covering urban and rural areas and different sectors including water, agriculture and disaster management, in order to examine: high-resolution climate change projection in Asia and how this can be used in planning appropriate adaptation responses; in-depth case studies of climate change projections, social, economic and environmental impact and vulnerability assessment and adaptation in rural Thailand and urban Philippines; cases across Africa for which climate data is less readily available and alternative approaches need to be adopted; the current situation amongst international donors; and emerging issues caused by climate change.